2022
DOI: 10.1097/ijg.0000000000002149
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With a Large Vertical Cup-to-Disc Ratio: Korean National Health and Nutritional Examination Survey

Abstract: Précis: Higher intraocular pressure, higher systolic blood pressure, and higher serum aspartate transaminase to alanine aminotransaminase level were risk factors associated with a large vertical cup-to-disk ratio (vCDR). Purpose: To identify risk factors for a large vCDR using data from the Korea National Health and Nutritional Examination Survey (2008–2012). Materials and Methods: Out of the total 29,322 participants aged 20 or older who participated in Korea National Health and Nutrition Survey (KHANES) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“… 58 Similarly, both low 20 , 59 and high blood pressure. 21 , 60 , 61 have been reported to associate with increased VCDR, although to our knowledge no studies have directly investigated the association of blood pressure with VCDR using nonlinear models. Although methods for nonlinear MR have been developed, 62 large-scale individual participant data in a one-sample setting is required, and such data are not currently available for POAG or VCDR.…”
Section: Discussionmentioning
confidence: 99%
“… 58 Similarly, both low 20 , 59 and high blood pressure. 21 , 60 , 61 have been reported to associate with increased VCDR, although to our knowledge no studies have directly investigated the association of blood pressure with VCDR using nonlinear models. Although methods for nonlinear MR have been developed, 62 large-scale individual participant data in a one-sample setting is required, and such data are not currently available for POAG or VCDR.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, studies have found optic discs to be significantly smaller in White and Hispanic populations compared to Asian and African-ancestry ones [ 28 , 29 ]. In studies on Asian populations, the risk factors for LCDR were found to be higher IOP, lower diastolic and higher systolic blood pressure, higher AST/ALT ratio, longer axial length, lower BMI, older age, male sex, and previous cataract surgery [ 30 , 31 ]. Notably, higher IOP emerged as the most significant determinant of a LCDR, similar to our findings in an African ancestry population [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, eyes with LCDR were more likely to experience elevated IOP, which is a major risk factor for POAG [ 32 , 33 ]. Studies have consistently found a significant correlation between higher IOP and LCDR, an indication of more severe glaucomatous damage [ 6 , 30 , 34 ]. Furthermore, research has shown that both IOP and VCDR have significant heritability and are genetically correlated with each other, as well as with the risk of POAG [ 6 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%